DYNAMIC ANT COLONY SYSTEM WITH THREE LEVEL UPDATE FEATURE SELECTION FOR INTRUSION DETECTION - MEHMOOD, TAHIR (2016)
Current era is known as the age of digital information and general mean of access to this information is computer networks. The use of network technology also make in formation insecure. Network intrusion detection systems play a vital role in network security and provide ways for restricting the unauthorized use of information or data. Internet security is one of the major issue in the current internet advancement. Con fidentiality, Integrity, and Availability of the data are the major concern for the secure systems. Intruder always try to breach the security of the systems by exploiting a num ber of parameters. Intrusion Detection System (IDS) is designed to detect intrusions in the data. Different detection methods have been used in these systems including Signature-based and Anomaly-based. The signature-based detection method is good to detect known attacks but it cannot detect novel attacks, as it only looks for signatures in the data which are fed in its knowledge base. On the other hand, Anomaly-based detection method is good to detect novel attacks, as it looks for exceptional patterns in the data on the cost of high numbers of false positives.